HYALURONIC ACID USING THE “FERN PATTERN TECHNIQUE” TECHNIQUE - SLEEP WRINKLES TREATMENT - Chiarelli, Murillo; Januzzi, Marcelo (Health and Society, 2023)
The skin, due to its protective role, suffers from exogenous factors (ultraviolet radiation, pollution and trauma) and endogenous factors (endocrine-metabolic diseases, alcohol and tobacco use), a sequence of functional alterations and/or structural problems that could harm its integrity, leading to dyschromia, dehydration, loss of elasticity and microvascular alterations. Wrinkles are an indicator of facial aging, with fault lines occurring in the skin, due to skin distortions resulting from facial expression or mechanical movements and compressions during sleep. Expression and sleep wrinkles differ in etiology, location and anatomical pattern. The skin during sleep undergoes compression, shear and tension forces that act on the face when we are in lateral or prone sleeping positions. Hyaluronic acid, since the 1990s, has been employed as a favorable temporary filler option for facial augmentation and for the regulation of various biological processes, such as skin repair, wound healing, tissue regeneration, reaching the prominent place regarding the treatment of wrinkles. This work aims to report a case of treatment of sleep wrinkles, in a female patient, only treated with fillers based on hyaluronic acid, with the “Fern Pattern Technique” technique with evolution of 2 years and with a single application.